IMPLEMENTASI KOPETENSI PERAWAT GIGI PADA PROGRAM USAHA KESEHATAN GIGI SEKOLAH (UKGS) DI SEKOLAH DASAR - Silfia, Aida; Wiryotinoyo, Mujiyono; Murbojono, Rahmat (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2014)
Nowadays, same elemtary school/SD which are located in Jambi City have already started getting the dental nurse graduates; to help schools on the Endeavor Program of School Dental Health (UKGS) Program for promotion, preventive and curative matters. This research is conducted to evaluate on the UKGS program in the implementation of promotation, preventive and curative actions. The types of the research used are qualitative methods and it is presented descriptively. The methods of collecting data are conducted by doing in-depth interviews to the personal-core informants and supported informants, non- participatory observation is conducted in the UKS room and the documentation study for the validity of the data is conducted by the triangulation methods and resources. The result showed that : (1) The promotion action was run well and it run according to the competences; (2) There are two competences of preventive core are not implemented for instance, the competence of how to rinse the mouth using fluorine substance and the other is the competence of doing the pit filling and fissure sealant. Meanwhile, the other two preventive competences have run well in accordance with its competence. They are the preventive competences have run well in accordance with its competence. They are the competences of theacing good teachnique in teeth brusing and claning/scraping the tartar; (3) The curative action was run in accordance with the competences, even though one of the competences could not be by the dental nurses. It is the competency of extracting single root permanent teeth, it was due to the lack of no license from the authority, the clinic or dentists. Keyword: The Implementation of Detal Nurse Competences, The Endeavor Programme of School Dental Health (UKGS)